The CD4+AT2R+ T cell subpopulation improves post‐infarction remodelling and restores cardiac function. Issue 8 (20th May 2015) - Skorska, Anna; von Haehling, Stephan; Ludwig, Marion; Lux, Cornelia A.; Gaebel, Ralf; Kleiner, Gabriela; Klopsch, Christian; Dong, Jun; Curato, Caterina; Altarche‐Xifró, Wassim; Slavic, Svetlana; Unger, Thomas; et al.
Abstract Myocardial infarction (MI) is a major condition causing heart failure (HF). After MI, the renin angiotensin system (RAS) and its signalling octapeptide angiotensin II (Ang II) interferes with cardiac injury/repair via the AT1 and AT2 receptors (AT1R, AT2R). Our study aimed at deciphering the mechanisms underlying the link between RAS and cellular components of the immune response relying on a rodent model of HF as well as HF patients. Flow cytometric analyses showed an increase in the expression of CD4+ AT2R+ cells in the rat heart and spleen post‐infarction, but a reduction in the peripheral blood. The latter was also observed in HF patients. The frequency of rat CD4+ AT2R+ T cells in circulating blood, post‐infarcted heart and spleen represented 3.8 ± 0.4%, 23.2 ± 2.7% and 22.6 ± 2.6% of the CD4+ cells. CD4+ AT2R+ T cells within blood CD4+ T cells were reduced from 2.6 ± 0.2% in healthy controls to 1.7 ± 0.4% in patients. Moreover, we characterized CD4+ AT2R+ T cells which expressed regulatory FoxP3, secreted interleukin‐10 and other inflammatory‐related cytokines. Furthermore, intramyocardial injection of MI‐induced splenic CD4+ AT2R+ T cells into recipient rats with MI led to reduced infarct size and improved cardiac performance. We defined CD4+ AT2R+ cells as a T cell subset improving heart function post‐MI corresponding with reduced infarction size in a rat MI‐model. Our results indicate CD4+ AT2R+ cells as a promising population for regenerative therapy, via myocardial transplantation, pharmacological AT2R activation or a combination thereof.